2020
DOI: 10.1002/htj.21984
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of natural convection of a non‐Newtonian nanofluid in an F‐shaped porous cavity

Abstract: This study numerically investigates the free convective heat transfer of a non‐Newtonian nanofluid through an F‐shaped porous cavity. The thermal conditions of the walls of the cavity are assigned as TC and TH for the cold right wall and the hot left wall, respectively, and the remaining walls of the cavity are assigned as insulated walls. The model for this investigation is designed, implemented, and analyzed by COMSOL Multiphysics. The Galerkin finite element method is used to model and solve the governing e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…They concluded that cooling performance increased with increasing volume fraction of the nanoparticles, especially at low Rayleigh numbers. Other researchers have presented non-uniform shapes such as a semiannulus trapezoidal configuration [20], complex C-shapes [21][22][23][24][25][26], annulus and semi-annulus shapes [22,23], and an F-shape [27].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that cooling performance increased with increasing volume fraction of the nanoparticles, especially at low Rayleigh numbers. Other researchers have presented non-uniform shapes such as a semiannulus trapezoidal configuration [20], complex C-shapes [21][22][23][24][25][26], annulus and semi-annulus shapes [22,23], and an F-shape [27].…”
Section: Introductionmentioning
confidence: 99%